Globalization, 9/11 and Cross-Cultural interaction: Locating Identity in Mohsin Hamid’s The Reluctant Fundamentalist: Exploring Identity in Mohsin Hamid’s The Reluctant Fundamentalist in a Globalized World (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The idea of identity is shaped with a sense of belongings of place, nation, culture, language and history. However, the idea of identity always flows with the rise of globalization as it promises a global space for all across the borders and boundaries. Migration of the people to the metropolis global space gradually has been increased and the new issues of immigration and immigrants have been arisen in the new era –the twenty-first century, especially after the 911. The paper aims at analyzing the issues of identity in Mohsin Hamid’s The Reluctant Fundamentalist (2007) which focuses on globalization, migration and cross-cultural encounter of the East and the West. The paper also tries to analyze the interracial love-relationship which explains the anti-globalization phenomenon in the post-911 scenario as it is represented in the novel. The protagonist of the novel is Changez, a young Pakistani boy who experiences the issues related to his race, religion, and region in post 911 America. Although Changez loves Erica and America as well, the response of both after 911 changes his mind. He feels alienated after being rejected by Erica and the American society. The paper focuses on exploring the idea of identity –individual and collective identity in response to globalization as native and immigrantforeigner. The paper also examines the psyche of shaping and reshaping the identity in the home and away from home –metropolis global place. The paper foregrounds the conflict of identity in response to cross-cultural interaction and its issues and challenges of adaptation, assimilation and acculturation in the global metropolis space. Furthermore, it investigates the genesis of identity and identity politics in the twenty-first century globalization in terms of prevalent global politics with reference to the novel.